Research ethics review for the use of anonymized samples and data: A systematic review of normative documents. (17th November 2017) - Phillips, Amicia; Borry, Pascal; Shabani, Mahsa
ABSTRACT: While the anonymization of biological samples and data may help protect participant privacy, there is still debate over whether this alone is a sufficient safeguard to ensure the ethical conduct of research. The purpose of this systematic review is to examine whether the review of an ethics committee is necessary in the context of anonymized research, and what the considerations in said ethics review would be. The review of normative documents issued by both national and international level organizations reveals a growing concern over the ability of anonymization procedures to prevent against reidentification. This is particularly true in the context of genomic research where genetic material's uniquely identifying nature along with advances in technology have complicated previous standards of identifiability. Even where individual identities may not be identifiable, there is the risk of group harm that may not be protected by anonymization alone. We conclude that the majority of normative documents support that the review of an ethics committee is necessary to address the concerns associated with the use of anonymized samples and data for research.